Preparation and characterisation of heat-treated and untreated red balau/ldpe composites / Ruth Anayimi Lafia-Araga - Araga, Ruth Anayimi Lafia (2013)

(untitled)
Red balau saw dust was heat-treated at 180°C and 200°C for one hour and compounded with low density polyethylene (LDPE) at 9, 20 and 37 wt%, then injection moulded. The composites specimens were exposed to different environments and characterised for the thermal, dynamic mechanical and mechanical properties. Thermogravimetric analysis revealed that heat treatment improved the thermal properties of the wood flour and its LDPE composites. Differential scanning calorimetric study showed that wood had no significant effect on the melting behaviour of the composites. However, the degree of crystallinity of composites containing untreated wood flour increased with increasing wood content, while the composites made from heat-treated wood flour, a decreasing trend was observed as the wood content increased. Dynamic mechanical analysis revealed that composites made from heat-treated wood flour exhibited higher storage and loss modulii than that of untreated wood. Lower tan delta values were observed in the heat-treated wood composites. The tensile modulus of the heat-treated wood flour/LDPE composites increased by 400% while the untreated wood flour/LDPE composites increased by 309% over the neat LDPE. This is because of the improved wetting of the heat-treated wood particles by the matrix, leading to a better interfacial adhesion. In addition, composites containing wood flour treated at 180°C showed higher tensile strength values than those made from untreated and 200°C treated wood flour. Furthermore, the flexural properties were found to increase with filler loading in the untreated wood composites, relative to those containing heat-treated wood flour. Peak load and critical stress intensity factor increased with wood content and treatment temperature. While the energy to failure and the critical strain energy release rate decreased with wood content, the values are vi highest in composites made from wood flour treated at 180°C. Incorporation of maleic anhydride grafted polyethylene (MAPE) into the composites led to improvements in the thermal and mechanical properties to various extents. In the composites containing untreated wood flour, incorporation of 8% MAPE provided the highest tensile strength and modulus, while 6% MAPE content recorded the maximum flexural modulus. All composites absorbed moisture to various extents with different levels of mechanical property deterioration. Composites made from heat-treated wood flour showed a reduction in water absorption up to 90% and offered better resistance to decline in properties. Heat-treated wood composites showed negligible effect of MAPE on the water absorption. For soil burial, composites made from heat-treated wood flour showed less fungal growth on the surface and better resistance to properties deterioration. Thermal and mechanical properties deteriorated with outdoor exposure. However, composites made from heat-treated wood flour showed better resistance to the elements of the outdoor environment than their untreated counterparts. It can be concluded that heat treatment of wood flour enhances the properties of wood thermoplastic composites with complementary ability to retain their mechanical properties following exposure to harsh outdoor environment. In general, the properties of the composites are not adversely affected on exposure to indoor environment. Therefore, using this product for domestic applications will be worthwhile.